Socio-Legal Study of Community Participation in Restorative Justice of Children in Conflict with the Law in Indonesia - Rochaeti, Nur; Muthia, Nurul (International Journal of Criminology and Sociology, 2021)
The state has the obligation and authority to protect children. This is regulated in Article 28 of the 1945 Constitution of the Republic of Indonesia, that everyone has the right to just recognition, guarantee, protection, and legal certainty as well as equal treatment before the law, namely that the State is obliged to protect every citizen regardless. The problem in this paper is how is the socio-legal study of restorative justice in the Juvenile Criminal Justice System in Indonesia. The method used in this research is a socio-legal research approach. This study found that the customary institution in Padang, West Sumatra is factually recognized in its existence in the customary criminal law of the Dua Puluah Customary Law. Moreover, the results showed that particularly in regulating the provisions of the material criminal law, in the Salapan Law (eight), and the Kanayatn Dayak community. implementing the restorative justice mechanism is resolved by deliberation and is family in nature in a Barukupm Adat forum, which involves all parties, both from functionaries, children of perpetrators and their families, victims and their families as well as witnesses who know the case, and pay attention to the rights of community members within the boundaries the agreed boundaries to be obeyed, based on the values and norms that exist in society. This study offers relevance in the context of non-legal settlement in cases of restorative justice in cases of children in conflict with the law in Indonesia. This study underscores expediency to provide greater space for customary entities to resolve children’s cases non-legally and to increase community participation in the resolution of legal cases involving children.ia.